The mobility problem in Britain: new findings from the analysis of birth cohort data - Bukodi, E; Goldthorpe, J; Waller, L; Kuha, J (Wiley, 2014)
Social mobility is now a matter of greater political concern in Britain than at any time previously. However, the data available for the determination of mobility trends are less adequate today than two or three decades ago. It is widely believed in political and in media circles that social mobility is in decline. But the evidence so far available from sociological research, focused on intergenerational class mobility, is not supportive of this view. We present results based on a newly‐constructed dataset covering four birth cohorts that provides improved data for the study of trends in class mobility and that also allows analyses to move from the twentieth into the twenty‐first century. These results confirm that there has been no decline in mobility, whether considered in absolute or relative terms. In the case of women, there is in fact evidence of mobility increasing. However, the better quality and extended range of our data enable us to identify other ‘mobility problems’ than the supposed decline. Among the members of successive cohorts, the experience of absolute upward mobility is becoming less common and that of absolute downward mobility more common; and class‐linked inequalities in relative chances of mobility and immobility appear wider than previously thought.